Values And Practices Of Business Ethics In Islamic Hospital Services - Muhammad Taufik Rahman; Surya Sukti (LP2M IAIN Palopo, 2026)
Hospitals are increasingly required to balance high-quality healthcare delivery with financial sustainability, a condition that often generates ethical dilemmas related to pricing, cost transparency, supplier selection, and service efficiency. These challenges are particularly salient for Islamic hospitals, where healthcare services are expected to reflect Islamic values in practice rather than merely adopting a Sharia label. This study aims to analyze how Islamic business ethics function as a foundational framework guiding managerial and service-related decisions in Islamic hospital settings. This research employs a qualitative conceptual approach based on a synthesis of recent empirical studies and a review of Sharia hospital regulatory frameworks in Indonesia. The analysis focuses on integrating Islamic business ethics across three dimensions: service ethics, organizational ethics, and transactional ethics. The findings indicate that consistent implementation of values such as amanah (trustworthiness), justice, compassion, and service excellence guided by maqāṣid al-sharīʿah enhances public trust, improves patient experience, and supports long-term hospital sustainability through reputation and service differentiation. However, practical constraints remain, including limited availability of halal medicines, resource demands for gender-sensitive services, and inconsistent SOP implementation. The study concludes that Islamic business ethics serve as a strategic mechanism for ethical sustainability. Practically, the findings highlight the need for maqāṣid-based SOPs, Sharia compliance audits, strengthened halal supply chains, and continuous ethics training to institutionalize Sharia values in daily hospital operations.